2008
DOI: 10.1002/jcop.20243
|View full text |Cite
|
Sign up to set email alerts
|

Personal lineages and the development of community psychology: 1965 to 2005

Abstract: The purpose of this study was twofold: (a) to examine and document the role of personal influence in the history of community psychology, and (b) to measure the field's inclusion of traditionally marginalized populations. In addition to presenting visually the genealogy of community psychology, results suggest that people have mattered in the development of the field independently from intellectual influence. Furthermore, community psychology has become more inclusive of ethnic minorities and women in position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Although we do not know how common it is, this kind of in-group networking has been found in one other psychological organization. A recent study of community psychologists found a high proportion of mentor -student lineages among leaders of that group (Fowler & Toro, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although we do not know how common it is, this kind of in-group networking has been found in one other psychological organization. A recent study of community psychologists found a high proportion of mentor -student lineages among leaders of that group (Fowler & Toro, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Using a ''lineage'' method for estimating the influence of key figures in community psychology, Fowler and Toro (2008) found that among 10 ''founders,'' Cowen had the largest number of ''descendents,'' including some of the most productive in terms of generating more descendents. It is useful to consider how Cowen accomplished all this, and it is certainly possible that his important conceptual writings at the beginning of the field (Cowen, 1973), as well as his commitment to action research throughout his career attracted many students to work with him.…”
Section: Discussionmentioning
confidence: 99%
“…Ten founders who made a significant impact on the field were identified along with their ''descendants.'' Founders included George Albee, Emory Cowen, Barbara Dohrenwend, George Fairweather, Ken Heller, Ira Iscoe, Jim Kelly, Rudolf Moos, Bob Newbrough, and Seymour Sarason (Fowler & Toro, 2008). Critics of this approach may suggest that this methodology creates the impression of elitism through its focus on pedigree and exclusion of contributions made by persons outside this lineage.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, recent analyses of lineages suggest that there are multiple sources of direct and indirect influence (Fowler & Toro, 2008). Those interested in mentoring can illuminate the varied styles of directing and assisting in career development.…”
Section: Social Network and Citation Analysesmentioning
confidence: 98%